Doctrine for Cybersecurity. - Mulligan, Deirdre K.; Schneider, Fred B. (Daedalus: Journal of the American Academy of Arts & Sciences)
A succession of doctrines for enhancing cybersecurity has been advocated in the past, including prevention, risk management, and deterrence through accountability. None has proved effective. Proposals that are now being made view cybersecurity as a public good and adopt mechanisms inspired by those used for public health. This essay discusses the failings of previous doctrines and surveys the landscape of cybersecurity through the lens that a new doctrine, public cybersecurity, provides.